Multidrug-Resistant Salmonella enterica Serovar Typhimurium Isolates Are Resistant to Antibiotics That Influence Their Swimming and Swarming Motility - Brian W. Brunelle (American Society for Microbiology, 2017)
ABSTRACT Motile bacteria employ one or more methods for movement, including darting, gliding, sliding, swarming, swimming, and twitching. Multidrug-resistant (MDR) Salmonella carries acquired genes that provide resistance to specific antibiotics, and the goal of our study was to determine how antibiotics influence swimming and swarming in such resistant Salmonella isolates. Differences in motility were examined for six MDR Salmonella enterica serovar Typhimurium isolates grown on swimming and swarming media containing subinhibitory concentrations of chloramphenicol, kanamycin, streptomycin, or tetracycline. Chloramphenicol and tetracycline reduced both swimming and swarming, though the effect was more pronounced for swimming than for swarming at the same antibiotic and concentration. Swimming was limited by kanamycin and streptomycin, but these antibiotics had much less influence on decreasing swarming. Interestingly, kanamycin significantly increased swarming in one of the isolates. Removal of the aphA1 kanamycin resistance gene and complementation with either the aphA1 or aphA2 kanamycin resistance gene revealed that aphA1, along with an unidentified Salmonella genetic factor, was required for the kanamycin-enhanced swarming phenotype. Screening of 25 additional kanamycin-resistant isolates identified two that also had significantly increased swarming motility in the presence of kanamycin. This study demonstrated that many variables influence how antibiotics impact swimming and swarming motility in MDR S. Typhimurium, including antibiotic type, antibiotic concentration, antibiotic resistance gene, and isolate-specific factors. Identifying these isolate-specific factors and how they interact will be important to better understand how antibiotics influence MDR Salmonella motility. IMPORTANCE Salmonella is one of the most common causes of bacterial foodborne infections in the United States, and the Centers for Disease Control consider multidrug-resistant (MDR) Salmonella a “Serious Threat Level pathogen.” Because MDR Salmonella can lead to more severe disease in patients than that caused by antibiotic-sensitive strains, it is important to identify the role that antibiotics may play in enhancing Salmonella virulence. The current study examined several MDR Salmonella isolates and determined the effect that various antibiotics had on Salmonella motility, an important virulence-associated factor. While most antibiotics had a neutral or negative effect on motility, we found that kanamycin actually enhanced MDR Salmonella swarming in some isolates. Subsequent experiments showed this phenotype as being dependent on a combination of several different genetic factors. Understanding the influence that antibiotics have on MDR Salmonella motility is critical to the proper selection and prudent use of antibiotics for efficacious treatment while minimizing potential collateral consequences.